CHARACTERISTICS OF STRUCTURE FORMATION IN COOKED SAUSAGE PRODUCTS USING SONOCHEMICAL TECHNOLOGIES - A. M. Yevtushenko; O. N. Krasulya; I. G. Krasheninnikova (Теория и практика переработки мяса, 2016)
This paper studies the features of formation of sausage product structure in the process of cooking. It is shown that the viscosity of sausage meat varies in a complex manner and has three characteristic areas. The characteristic parameters that determine the formation of the structure of sausages for each area were found. It is established that the use of the cavitation brine gives the finished product a gentle consistence, elasticity and distinct taste that makes it more preferable for the consumer.